[PP.11.10] CARDIOVASCULAR RISK ASSESSMENT, CLINICAL CHARACTERISTICS, AND COMORBIDITIES OF HOSPITALIZED PATIENTS WITH HYPERTENSION AND ANAEMIA. (September 2017) - Olteanu, D.; Suta, T.; Ungureanu, R.; Dediu, G.; Diaconu, C.; Balaceanu, A.
Abstract : Objective: The aim of the study was the assess the cardiovascular risk of the hospitalized patients with hypertension and anaemia. Design and method: The retrospective study included 109 patients with hypertension and anaemia admitted to clinical emergency hospital between August-November 2016. Results: The average age was 73.64 with a standard deviation 11.39. The minimum age was 43 and maximum age were 97. From 109 patients 52.29% were female and 47.70% were male. According to hypertension readings the following distribution was noticed: grade I: 23.85%; grade II: 38.53%; grade III: 32.11%. The causes of anaemia were: iron-deficiency 20.18%; macrocytic 21.10%; normochromic normocytic 56.88%; due to blood lost 0.91%. The anaemia was classified by severity in mild (haemoglobin 10–12 g/dl for women in 38.53% of cases and 13–15 g/dl for men in 25.68%), moderate (haemoglobin 7–10 mg/dl in 27.52%) and severe (haemoglobin <7 mg/dl in 8.25%.) Comorbidities: According MDRD equation, chronic kidney disease was encountered in 83.49%; grade II 26.60%; grade III 39.44%; grade IV 11.00%. Hypertensive cardiomyopathy with echocardiographic diastolic dysfunction was presented at 36.69% patients; from these patients electrocardiographic signs of left ventricle hypertrophy were found in 1.83% cases. Diabetes mellitus was found in 21.10% cases. From female patients 43.11% had CKD and from male patients 39.44% had CKD. According to European Score charts the patients included in our study are distributed following the next categories: low risk 4.52%; medium risk 38.53%, high risk 27.52% and very high risk 11.92%. Conclusions: The patients with hypertension and anaemia had a medium and high risk of cardiovascular disease (p = 0.04). CKD was the most common comorbidity at these patients.